(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Targeted drug delivery has revolutionized modern medicine by enabling the precise delivery of therapeutics to specific sites while minimizing systemic side effects. This comprehensive review explores recent advancements in targeted drug delivery systems, focusing on nanotechnology-based approaches, stimuli-responsive carriers, and innovative targeting strategies. Nanoparticles, including liposomes, polymeric nanoparticles, and inorganic nanoparticles, offer enhanced drug solubility and targeted delivery to specific tissues or cells. Stimuli-responsive drug carriers respond to environmental cues, allowing for controlled drug release. Targeting strategies employ ligands to bind to receptors on target cells, enabling precise delivery of therapeutics. Applications span various diseases, including cancer, neurological disorders, infectious diseases, and chronic conditions. Despite challenges such as biocompatibility and regulatory considerations, targeted drug delivery holds promise for personalized medicine, improving therapeutic efficacy, and patient outcomes.